2011
DOI: 10.1007/s11207-011-9848-9
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study on the Morphology of Rays and Dynamics of Blobs in the Wake of Coronal Mass Ejections

Abstract: In this paper, with a survey through the Large Angle and Spectrometric Coronagraph (LASCO) data from 1996 to 2009, we present 11 events with plasma blobs flowing outwards sequentially along a bright coronal ray in the wake of a coronal mass ejection. The ray is believed to be associated with the current sheet structure that formed as a result of solar eruption, and the blobs are products of magnetic reconnection occurring along the current sheet. The ray morphology and blob dynamics are investigated statistica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 31 publications
1
24
0
3
Order By: Relevance
“…So for the time being, studying the brightness distribution is the only approach via which more or less, we are able to look into the geometric structure and physical properties of the CS. In addition to the thermal halo, it is possible that, like the case of the helmet streamer, the CME/flare CS itself is actually very thin and embedded in a thick plasma sheet that could be recognized according to the brightness, and the CS thickness is actually much smaller than that of the plasma sheet (e.g., see also Song et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So for the time being, studying the brightness distribution is the only approach via which more or less, we are able to look into the geometric structure and physical properties of the CS. In addition to the thermal halo, it is possible that, like the case of the helmet streamer, the CME/flare CS itself is actually very thin and embedded in a thick plasma sheet that could be recognized according to the brightness, and the CS thickness is actually much smaller than that of the plasma sheet (e.g., see also Song et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…After having analyzed the LASCO data obtained in the time interval between 1996 and 2009, Song et al (2012) found more plasma blobs flowing inside the post-CME CS. The speeds of these blobs spread over the range from 200 to 10 3 km s −1 .…”
Section: Upward Reconnection Outflowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al [62] conducted a survey through the LASCO data obtained in 2007 and did find 10 multi-blob events with 106 blobs in total. All events last for 3-4 d. In Figure 5 velocity profiles for all blobs observed in Song et al [70] are plotted together. From this figure and other plots not shown here, it can be seen that all velocities increase monotonically with radial distance, and vary in a relatively small range of < 300 km s 1 .…”
Section: Persistent Releases Of Streamer Blobs and Diagnostics Of Neamentioning
confidence: 96%
“…Velocity-distance (in units of solar radii) profiles for the 45 post-CME blobs collected by Song et al [70] (black circles) and the 106 streamer blobs (red pluses) given by Song et al [62]. A blue line is drawn to separate their velocity distributions, which is given by the average of the polynomial fittings to the two groups of velocity measurements and expressed as v=0.1r 2 +13.7r+246 with v and r in units of km s 1 and Rs, respectively.…”
Section: Figurementioning
confidence: 99%